2017
DOI: 10.17235/reed.2017.4645/2016
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to predict the presence of colorectal cancer in a blood test? A probabilistic approach method

Abstract: We showed that a colorectal cancer predictive character exists in blood which can be quantified by an interaction index of several blood parameters. The design and development of interaction indexes of blood parameters constitutes an interesting research line for the development and improvement of programs for the screening of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Lin et al [2] reported that an elevated PLT count might influence the development of colorectal cancer, and the preoperative PLT count might be a predictive factor of survival in patients with colorectal cancer. Navarro et al [19] showed the presence of a predictive characteristic of colorectal cancer in the blood that can be measured with an interaction index of various blood parameters, such as PLT counts and levels of hemoglobin, fibrinogen, hematocrit, total leukocytes, eosinophils, and neutrophils. The current study showed that patients with negative lymph nodes and venous invasion had significantly lower PLT counts than patients with positive lymph nodes and venous invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [2] reported that an elevated PLT count might influence the development of colorectal cancer, and the preoperative PLT count might be a predictive factor of survival in patients with colorectal cancer. Navarro et al [19] showed the presence of a predictive characteristic of colorectal cancer in the blood that can be measured with an interaction index of various blood parameters, such as PLT counts and levels of hemoglobin, fibrinogen, hematocrit, total leukocytes, eosinophils, and neutrophils. The current study showed that patients with negative lymph nodes and venous invasion had significantly lower PLT counts than patients with positive lymph nodes and venous invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [4] reported that increased PLT count might play some role in the progress of colorectal cancer and preoperative PLT count might be a prognostic indicator in the colorectal cancer patients. Navarro et al [26] showed that a colorectal cancer predictive character exists in blood which can be quanti ed by an interaction index of several blood parameters including PLT counts, brinogen, total leukocytes, neutrophils, and hemoglobin, hematocrit and eosinophil levels. In our study,…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumour cells secrete VEGF, tissue factor (TF), cancer procoagulant (CP) and tumour necrosis factor (TNF) leading to a hypercoagulable state of blood and increased plasma FIB levels [11]. FIB forms fibronectin through a series of reactions and acts as a scaffold for the growth, infiltration and metastasis of malignant tumour cells [4] [12]. Palumbo [13] found that the incidence of metastasis was significantly reduced in FIB-deficient mice, but primary tumour growth was not affected.…”
Section: Fib and Colorectal Cancermentioning
confidence: 99%